Optimization of Good Agricultural Practices For Callina Papaya Farming Business - Cipta Wijaya; Nurliza Nurliza; Shenny Oktoriana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Good agricultural practices (GAP) have become a minimum requirement for the implementation of sustainable agriculture and food security. However, the application of GAP still faces several obstacles such as not using quality seeds, undone filing, excessive use of fertilizers, planting that is not in accordance with the recommendations, harvesting and post-harvest activities that do not comply with fruit quality management standards, and so forth. This study was aimed to empirically identifying the sustainability of the application of GAP in papaya farming and optimizes business practices in the GAP for papaya farmer. The number of respondents had taken as many as 35 people through non-purposive sampling with in-depth interview techniques. Research method used was descriptive quantitative using Rap-Papaya and descriptive qualitative with fishbone diagram. The results of the study indicated that the economic dimension with the most sensitive attributes, namely supervision, record keeping, and traceability, needs to be improved. Therefore, the stakeholders need to strengthen farmer groups, do the provision of incentives in the form of inputs for farmers, conduct training and mentoring of farm records on a regular basis, create partnership with the private sectors, establish participatory empowerment with regular meetings, and formulate note taking as an input assistance requirement.